Training on Creating Interactive Learning Media Using Canva and PowerPoint Applications for PGSD Students - Prananda, Gingga; Hendrilia, Yudi; Ubaidillah, Ubaidillah; Fauzi, Muhammad Sukron; Ahyani, Edi; Ayu, Dwi Hadita (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Training on creating interactive learning media is an important strategy for enhancing the competence of prospective teachers in the digital era. This study aims to improve the skills of students in the Elementary School Teacher Education Program (PGSD) at the Nahdlatul Ulama University of West Sumatra in designing interactive learning media using Canva and PowerPoint applications. The training activity was attended by 50 third-semester students who had completed the Digital-Based Learning Media course for elementary schools (SD/MI). The method used in this activity was a practical workshop, which included demonstrations, hands-on practice, and evaluation of student work. The training results showed a significant improvement in the students' ability to use Canva and PowerPoint features to create engaging, creative, and relevant learning media for elementary school students. Based on the evaluation results, students achieved an overall average score of 4.35, categorized as good to excellent, particularly in terms of independence and design creativity. This training also boosted the students' confidence in teaching and their ability to collaborate effectively. Therefore, this training has proven to positively contribute to the development of pedagogical and technological competencies of PGSD students in creating innovative and enjoyable interactive learning media for elementary school students.